An Integrated Circular Supply Chain Framework to Enhance Malaysian Business Performance - Harun, Shariff; Senawi, Azhan Rashid (Information Management and Business Review, 2024)
Businesses rely on supply chain management to suit the needs of global and multigenerational consumers. However, the current linear manufacturing and distribution supply chain strategy has been regarded as the source of dangerous waste generation, environmental deterioration, and the global warming phenomenon. In mitigating this issue, circular supply chain management, a practical integration model, is seen as the solution as it helps to reduce material flows and supply chain waste. Unfortunately, the fundamental mechanisms that can support its effective execution have not been comprehensively examined, hindering its complete incorporation into company strategy. Thus, to overcome this knowledge gap and improve organizational understanding, this study uses the systematic reviews and meta-analyses extension for scoping reviews (PRISMA-ScR) procedure to investigate the characteristics, enablers, and barriers of circular supply chain management. The study found five interconnected key structures: government, industry stakeholders, corporate management, end users, and financial institutions, all of which play important roles in the successful implementation of a circular supply chain strategy. As a result, close collaboration across the five identified stakeholders is essential to enable successful implementation. This study’s objective is to the United Nations Sustainable Development Goals (SDGs) 8, 9, and 12, which aim to promote peace and prosperity for people and the planet both now and in the future.